Oral language skills and psychosocial competence in early school-aged children of different language profiles - Ralli, Asimina M.; Kazali, Elena; Karatza, Elissavet (Psychology: the Journal of the Hellenic Psychological Society, 2021)
The role of language in children’s psychosocial competence is fundamental, as it contributes to the emotional and behavioral self-regulation as well as to the interpersonal relationships. In line, recent research evidence emphasizes that children with Developmental Language Disorder (DLD), who have significant language deficiencies, often face psychosocial difficulties that challenge academic/school achievement. The aim of the present study is to provide the most detailed description of oral skills (phonology, semantics, morphology, pragmatics and narrative discourse) and psychosocial adaptation (social, school, emotional, and behavioral problems) as well as to investigate the interaction of the above skills, which has not yet been adequately studied in children with and without language deficits. Thirty-six children aged 6 years participated in the study. Half of the participants were children with DLD and half were typically developing children. All the children were evaluated on their non-verbal intelligence as well as on vocabulary, phonological awareness, morphology, pragmatic and narrative skills with the use of a standardized language assessment battery, LOGOMETRO. The children’s psychosocial competence was assessed with the Psychosocial Competence Test, which was completed by the teachers of the children who participated in the study. Mixed variance analysis was applied to test (a) the main effects of the group of children and the type of measurement as well as (b) the interaction of these two. The results showed statistically significant differences in the areas of oral language and psychosocial skills between and within the groups. In addition, there were significant correlations between the language performance and the psychosocial skills in children with DLD. The findings are discussed in terms of their theoretical and educational implications for early detection and intervention.